PLA/PLGA-Based Drug Delivery Systems Produced with Supercritical CO2-A Green Future for Particle Formulation? - Gauri Gangapurwala; Antje Vollrath; Alicia De San Luis; Ulrich S. Schubert (MDPI AG, 2020)
Supercritical carbon dioxide (SC-CO2) can serve as solvent, anti-solvent and solute, among others, in the field of drug delivery applications, e.g., for the formulation of polymeric nanocarriers in combination with different drug molecules. With its tunable properties above critical pressure and temperature, SC-CO2 offers control of the particle size, the particle morphology, and their drug loading. Moreover, the SC-CO2-based techniques overcome the limitations of conventional formulation techniques e.g., post purification steps. One of the widely used polymers for drug delivery systems with excellent mechanical (Tg, crystallinity) and chemical properties (controlled drug release, biodegradability) is poly (lactic acid) (PLA), which is used either as a homopolymer or as a copolymer, such as poly(lactic-co-glycolic) acid (PLGA). Over the last 30 years, extensive research has been conducted to exploit SC-CO2-based processes for the formulation of PLA carriers. This review provides an overview of these research studies, including a brief description of the SC-CO2 processes that are widely exploited for the production of PLA and PLGA-based drug-loaded particles. Finally, recent work shows progress in the development of SC-CO2 techniques for particulate drug delivery systems is discussed in detail. Additionally, future perspectives and limitations of SC-CO2-based techniques in industrial applications are examined.